Complementary treatment in endometriosis - Woźniak, Piotr; Ziółkowski, Paweł; Stetkiewicz, Tomasz; Pięta-Dolińska, Agnieszka; Oszukowski, Przemysław (Menopause Review/Przegląd Menopauzalny, 2012)
Patients very often search for alternative ways of treatment. They find scientifically based treatments for many disease entities. One of those illnesses is endometriosis. Endometriosis is a problem for a huge number of women, for example according to American sources, in the USA it occurs in about 10% of women’s population in the child-bearing period. It is a chronic illness that has a significant impact on the quality of women’s life and their fertility. Despite a tremendous development of pharmacotherapy and surgical techniques in recent years, treatment of endometriosis remains ineffective in about 20–40% of women. In the case of endometriosis, the diet, supplementation of vitamins and micro- and macronutrients are important both as a risk factor for the disease and as a part of complementary therapy. Acupuncture, herbs and TENS are used as complementary therapies. This paper presents how these methods work in the case of endometriosis, based on the existing scientific evidence.